Contemporary ethnic problems in the Republic of Macedonia - Stawowy-Kawka, Irena (Balcanica Posnaniensia. Acta et studia, 2001)
on the question of Macedonian national identity and relations among the ethnic groups inhabiting the state. The author addresses disputes concerning the status of the Macedonian nation and their influence on the country’s political situation after independence. The aim of the study is to present the sources of nationality conflicts, characterize the state’s ethnic structure, and assess the challenges associated with building a democratic multinational society. The analysis is based on a historical-political method employing statistical data, political documents, and relevant scholarly literature. The author notes that in the mid-1990s ethnic Macedonians constituted approximately two-thirds of the country’s population, while national minorities accounted for a significant proportion of society. The article discusses the historical and political context of Macedonian statehood, disputes concerning minority rights, and competing interpretations of the region’s history. The conclusions emphasize that Macedonia’s stability depends on the successful reconciliation of the interests of different national groups and on recognition of the state’s multiethnic character. Unresolved identity issues and tensions between the majority population and minorities remain among the most important challenges facing the development of a democratic Macedonian state.